The Past and Present of Instructional Design in Online Learning: Trends and Emerging Directions - Özkan, Adem; Çevik, İsak; Saylan, Esin; Çakıroğlu, Ünal (International Review of Research in Open and Distributed Learning, 2025)
With the rapid evolution of online learning, driven by technological advancements and the global transition to distance education during the COVID-19 pandemic, the demand for effective instructional design models has become increasingly critical. This study conducted a systematic mapping analysis of instructional design models tailored for online learning environments to offer a comprehensive classification and evaluation of these models. The analysis delved into the theoretical underpinnings, practical applications, and implications for educators and instructional designers. Models were categorized based on instructional conditions, desired learning outcomes, and theoretical-methodological frameworks, and thus provided a structured approach to understanding their relevance and effectiveness. The findings underscored a paradigm shift from traditional, content-centric frameworks toward adaptive, learner-centered designs that emphasize motivation, social interaction, personalization, and technological integration. Additionally, this study offered practical recommendations for selecting and implementing models that align with the dynamic needs of learners and supported future advancements in instructional design, to foster innovation and effective learning in diverse educational contexts.